Panchayati Raj and Tribal Education:The Case of Paniyas in Wayanad - Swamy, Raju Narayana; Hema, S. (SFIMAR Research Review, 2011)
It is said that India lives in her villages. Inspite of rapid pace of urbanization, around 70% of the population of India lives in villages and is employed in the primary sector. Inequities in terms of educational facilities and resources, rural poverty, environmental degradation etc are some key issues vital in India. The 73rd Constitutional Amendment is a great initiative to establish institutions of local self government with the task to prepare and implement plans for economic development and social justice. However the situation of scheduled tribes has continued to be more or less same. They are among the most socially and educationally disadvantaged groups in India. The pattern of educational achievements has been different for the general and scheduled tribe population with the latter never has been an integral part of the mainstream society. This contrast in educational achievements for the general and STs is crucial in assessing their respective development experiences and reform programmes. Exclusion from basic education for the tribes is a complex socio-political process that has multiple roots and causes. Kerala has launched in mid-1996 a unique decentralized planning experiment to enhance participatory democracy and quality of life of the local people. The aim of this paper is to take up the questions regarding tribal education in Kerala with special reference to Wayanad. The study attempts to portray the dismal state of literacy among Paniyas, a tribal community in Wayanad and factors contributing to the generally low literacy rates and educational attainment among them.